Optimization of the Oligonucleotide Ligation Assay, a Rapid and Inexpensive Test for Detection of HIV-1 Drug Resistance Mutations, for Non-North American Variants - Beck, Ingrid A. (2008)
OBJECTIVE: We evaluated the feasibility of the oligonucleotide ligation assay (OLA), a specific, sensitive, and economical ligase-based point mutation assay designed to detect HIV-1 drug–resistance mutations at 12 codons of HIV-1 subtype B pol, for potential use in resource-poor settings. METHODS: Specimens from HIV-1–infected individuals collected by 7 international laboratories, including subtypes A, B, C, D, F, G, J, and recombinants AE and AG, were tested by the OLA developed for HIV-1 subtype B. Common polymorphisms that interfered with reactivity of the OLA were identified and modified probes designed and evaluated. RESULTS: 92.5% (2410) of 2604 codons in specimens from 217 individuals were successfully genotyped by the subtype B OLA. A high rate (range 8.3%–31.2%) of indeterminate results (negative OLA reaction for both mutant and wild type) was observed for 5 codons. Modified probes at reverse transcriptase codons 151 and 184 and protease codon 90 increased the rate of valid OLA to 96.1%. CONCLUSIONS: The OLA designed for HIV-1 subtype B genotyped most pol codons in non-B subtypes from Asia and Africa but was improved by addition of several modified probes. International laboratories experienced in molecular techniques were able to perform the OLA.